Financial management : concepts, analysis and capital investments - Olowe, R. A. (Rufus Ayodeji) (Lagos : Brierly Jones Nigeria, c1997., 1997)
Covers the theoretical and practical aspects of financial management in relation to the Nigerian environment in terms of legal, tax, and commercial framework in which businesses operate.
Includes bibliographical references and index.
oif 06/03/15
Loan
Keywords: Corporations -- Nigeria -- Finance; Corporations -- Finance; Finance -- Nigeria; Management -- Nigeria